PP-004 A prospective evaluation of acetic acid enhanced chromoendoscopy in the identification of dysplasia within Barrett's oesophagus. (23rd September 2015) - Longcroft-Wheaton, G R; Mead, R; Duku, M; Poller, D; Bhandari, P
Abstract : Introduction: The current accepted standard of care in Barrett's surveillance has involved the routine collection of large numbers of non-targeted biopsies (Seattle protocol). This is time consuming, expensive and can miss significant abnormalities. Acetic acid has been demonstrated to be effective in identifying areas of metaplasia, with an increasing number of endoscopists questioning whether it has a role in the identification of dysplasia. We aim to evaluate the use of acetic acid (AA) chromoendocopy in the assessment of Barrett's neoplasia. Methods: We prospectively collected data on patients with Barrett's oesophagus who had undergone chromoendoscopy between July 2004 and November 2009. All procedures were performed by a single experienced endoscopist (PB) using fujinon (EG-590) gastroscopes and EPX 4400 processor. The mucosae was examined with white light (WLI) high-resolution endoscopy (HRE) and visible abnormalities recorded. Acetic acid (2.5%) dye spray was then performed, and all additional visible abnormalities were characterised and targeted biopsies taken. Quadrantic biopsies at 2 cm intervals of the remaining Barretts epithelium were then taken in all patients. The chromoendoscopic diagnosis was compared with the histological diagnosis to evaluate the sensitivity and specificity of AA chromoendoscopy. Results: We performed a total of 335 procedures on 173 patients. The mean age of the group was 67 years with 75% males. The prevalence of dysplasia or malignancy in this cohort was 46%. The mean length of Barrett's oesophagus was 3.7 cm (range 2–15) Pearson's rank correlation showed a statistically significant correlation between the chromoendoscopic targeted histology and the actual histology (qudrantic+targeted histology) (r=0.9). We applied the Chi2 test to our data and found a significant difference between visible neoplasia seen on WLI vs AA chromoendoscopy (p<0.001) (see Abstract 004 ). The sensitivity was 93% with a specificity of 80% for all neoplasia Conclusion: This is the largest world series of acetic acid (AA) chromoendoscopic evaluation of Barrett's oesophagus. It demonstrates that dye spray improves the neoplasia detection rate by 2.4-fold, with an excellent correlation with the overall diagnosis. this questions the validity of current surveillance strategy of multiple random biopsies.